Recipient body mass index and age interact to impact survival after heart transplantation. (15th October 2014) - Weber, Daniel J.; Hashmi, Zubair A.; Gracon, Adam S. A.; Hellman, Yaron M.; Patel, Ankur J.; Wozniak, Thomas C.; Wang, I‐wen
Abstract Although recipient body mass index (BMI) and age are known risk factors for mortality after heart transplantation, how they interact to influence survival is unknown. Our study utilized the UNOS registry from 1997 to 2012 to define the interaction between BMI and age and its impact on survival after heart transplantation. Recipients were stratified by BMI: underweight (<18.5), normal weight (18.5–24.99), overweight (25–29.99), and either moderate (30–34.99), severe (35–39.99), or very severe (≥40) obesity. Recipients were secondarily stratified based on age: 18–40 (younger recipients), 40–65 (reference group), and ≥65 (advanced age recipients). Among younger recipients, being underweight was associated with improved adjusted survival (HR 0.902; p = 0.010) while higher mortality was seen in younger overweight recipients (HR 1.260; p = 0.005). However, no differences in adjusted survival were appreciated in underweight and overweight advanced age recipients. Obesity (BMI ≥ 30) was associated with increased adjusted mortality in normal age recipients (HR 1.152; p = 0.021) and even more so with young (HR 1.576; p < 0.001) and advanced age recipients (HR 1.292; p = 0.001). These results demonstrate that BMI and age interact to impact survival as age modifies BMI–mortality curves, particularly with younger and advanced age recipients.